2016
DOI: 10.1007/s40846-016-0139-7
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Alterations for Various Stent Configurations in Idealized Wide-neck Basilar Tip Aneurysm

Abstract: Stent-assisted coiling technology is widely used in the treatment of intracranial aneurysms. However, differences among various stent configurations have not been fully characterized. This study investigates the hemodynamic effects for various stent configurations. Computational fluid dynamics simulations were performed on an idealized wide-neck basilar tip aneurysm model, which was constructed from digital subtraction angiography images with a virtual stenting technique. The orifice of the aneurysm was tilted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…For the posterior circulation aneurysms, especially the basilar tip aneurysm, various stent configurations including half-Y Y crossbar and T could be implanted. Previous hemodynamic studies demonstrated obvious differences between Enterprise stent configurations in wide-necked basilar tip aneurysms [8]. However, compared to the Enterprise stent, the LVIS stent has lower recanalization rate and a higher occlusion rate [2,3].…”
Section: Am J Biomed Sci and Resmentioning
confidence: 98%
See 1 more Smart Citation
“…For the posterior circulation aneurysms, especially the basilar tip aneurysm, various stent configurations including half-Y Y crossbar and T could be implanted. Previous hemodynamic studies demonstrated obvious differences between Enterprise stent configurations in wide-necked basilar tip aneurysms [8]. However, compared to the Enterprise stent, the LVIS stent has lower recanalization rate and a higher occlusion rate [2,3].…”
Section: Am J Biomed Sci and Resmentioning
confidence: 98%
“…In our simulations, a novel virtual stenting workflow [8,9] was used to deploy the Enterprise and LVIS stents (Figure 1). The simulation consists of the following three steps: (1) Pre-processing, which separates the parent artery from the aneurysm, and produces a simplex mesh structure along the vessel centerline position;…”
Section: Stent Modeling and Deploymentmentioning
confidence: 99%
“…Ideal models are often based on assumed geometry with anatomically relevant dimensions used to study the morphological patterns [129][130][131][132][133] and Neuroendovascular device efficacy. 134,135 Some of the ideal model geometries are actually constructed from averaging of patientspecific dimensions across a specific population to compare the relevance of gender, 136 morphology 137 or complex cases of IA. 138 Patient-specific models are often constructed from DSA images, 139 and then converted to volume meshing suitable for any adequate CFD solver.…”
Section: Classification Of Ia Cfd Modelsmentioning
confidence: 99%
“…The two types of FDs with most clinical data in the literature are the Pipeline Embolization Device [6,7] (PED; Covidien Vascular Therapies, Mansfield, MA, USA) and Silk stent [8] (Balt, Montmorency, France). Different FD configurations will have an observable effect on the hemodynamics [9]. In this paper, the focus will be placed on PED.…”
Section: Introductionmentioning
confidence: 99%
“…9) where v  = inflow velocity vector on the neck orifice (m s -1 ), A  = area vector normal to the neck orifice (mm 2 ). The area-weighted average of γ average is defined as…”
mentioning
confidence: 99%